Job satisfaction and turnover intention : is there a significant difference between public and private preschools? - Kristín Valgerður Ellertsdóttir 1982- (2016)
The main focus of this thesis is job satisfaction and turnover intention between the public and the private sectors. The researcher has a background as an educated preschool teacher and therefore was interested in whether job satisfaction differed between private and public preschools. The literature review analyzes job satisfaction and how it connects with turnover, as well as its importance for employees and the organization as a whole. Preschools are known for high turnover rates, which will be analyzed further within the literature review. In addition, there is potentially a difference in job satisfaction and turnover between sectors. Overall, both the public and private sectors have positive and negative characteristics, which provide learning opportunities. The research was conducted within the timeframe of November 2015 to May 2016. In the private sector, the organization of Hjallastefnan.ehf granted permission to conduct the research within their preschools. With regards to the public sector, the municipality of Hafnarfjörður also allowed contacting preschools for research purposes. The researcher conducted online quantitative research and used the standardized European Employee Index questionnaire, which has been used to measure job satisfaction within Europe with good results. The participants were given a link via e-mail and had three weeks to complete the survey. Subsequently, the results were interpreted with the SPSS application. The results from the research indicated that there is no significant difference in job satisfaction and turnover intention between the sectors. Both sectors have satisfied employees with no intention of leaving in the near future. However, the participation in the questionnaire was less than expected and therefore the results might have differed if the number of participants had been higher. The main focus of this thesis is job satisfaction and turnover intention between the public and the private sectors. The researcher has a background as an educated preschool teacher ...